2017
DOI: 10.1534/genetics.116.198820
|View full text |Cite|
|
Sign up to set email alerts
|

The NCA-1 and NCA-2 Ion Channels Function Downstream of Gq and Rho To Regulate Locomotion in Caenorhabditis elegans

Abstract: The heterotrimeric G protein G positively regulates neuronal activity and synaptic transmission. Previously, the Rho guanine nucleotide exchange factor Trio was identified as a direct effector of G that acts in parallel to the canonical G effector phospholipase C. Here, we examine how Trio and Rho act to stimulate neuronal activity downstream of G in the nematode Through two forward genetic screens, we identify the cation channels NCA-1 and NCA-2, orthologs of mammalian NALCN, as downstream targets of the G-Rh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 83 publications
(133 reference statements)
6
48
0
Order By: Relevance
“…Recently, we identified the cation channels NCA-1 and NCA-2 as downstream targets of this G q -Rho pathway. Specifically, we found that mutations in genes that encode accessory subunits of the NCA channels (u nc-79 , unc-80 ) or in the NCA channels per se ( nca-1; nca-2 ) suppress the neuronal phenotypes of activated G q and activated Rho [12]. Moreover, mutations in the Rho-NCA pathway suppress the loopy posture of the activated G q mutant more strongly than do mutations in the canonical PLCβ pathway [12].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we identified the cation channels NCA-1 and NCA-2 as downstream targets of this G q -Rho pathway. Specifically, we found that mutations in genes that encode accessory subunits of the NCA channels (u nc-79 , unc-80 ) or in the NCA channels per se ( nca-1; nca-2 ) suppress the neuronal phenotypes of activated G q and activated Rho [12]. Moreover, mutations in the Rho-NCA pathway suppress the loopy posture of the activated G q mutant more strongly than do mutations in the canonical PLCβ pathway [12].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we found that mutations in genes that encode accessory subunits of the NCA channels (u nc-79 , unc-80 ) or in the NCA channels per se ( nca-1; nca-2 ) suppress the neuronal phenotypes of activated G q and activated Rho [12]. Moreover, mutations in the Rho-NCA pathway suppress the loopy posture of the activated G q mutant more strongly than do mutations in the canonical PLCβ pathway [12]. Like mutations in the Rho-NCA pathway, grk-2 mutants also strongly suppress the loopy posture of an activated G q mutant (Figs 1A, 4D and 4E), suggesting that grk-2 may affect signaling through the Rho-NCA pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations